Corrigendum to "The use of cloud-based learning media and its implications for elementary students' digital literacy" - Ragil Dian Purnama Putri; Fajar Kurnia Al Farisi; Tri Lestari; Safika Maranti; Agus Kichi Hermansyah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This corrigendum addresses an error in the author byline and associated metadata of the originally published article. The fifth author's name was published as 'Agus Kichi Firmansyah' when it should have appeared as 'Agus Kichi Hermansyah'. The author's ORCID iD is https://orcid.org/0000-0002-1172-0869. The authors sincerely apologize for this oversight and any inconvenience it may have caused. The online version of the article and its associated metadata have been amended to reflect this correction.